Bibliometric Analysis: The Development of Research and Publications on Sustainable Development Goals (SDGs) and Their Impact on Investment - Maulidia, Nuke (PT Inovasi Pratama Internasional, 2025)
Purpose: This study aims to analyse literature related to Sustainable Development Goals (SDGs) and their impact on investment using bibliometric analysis. Design/Methodology/Approach: The study utilises 41 articles related to SDGs and investment collected from the Scopus database. The bibliometric analysis includes keyword analysis, trend analysis, and density visualisation. Findings: The research results indicate four main topic clusters: 1) carbon dioxide, climate change, economic development, etc.; 2) foreign direct investment, governance, private sector, etc.; 3) economic and social effects, emerging economies, environmental quality, etc.; 4) alternative energy, environmental economics, spatiotemporal analysis. The topics of